Professional Identity of Journalist in Hybrid Media System - A. Yu. Kolianov (Дискурс, 2020)
Introduction. This paper analyzes how the journalists’ professional identity is changing in the reality of hybrid media system. Understanding of journalists’ professional identity is based upon the conclusion that information environment is building the journalists’ characters today. The mixing of media and digital technologies leads to the hybridization of media in its basis. Journalist’s activities within the present media system lead to contradictory and sometimes odd effects.Methodology and sources. The comparison and generalization of expert interviews, public opinion polls and official documents and media texts were applied. Content analyses of journalist’s papers and discourse analysis of theoretical studies were also used to study the professional identity of journalists.Results and discussion. In this paper we try to answer how does the global digital environment affect the conditions, goals and effects of journalist’s professional activities? How the journalist’s professional activity changes? What characteristics of journalist should be included in the professional identity that appears in the hybrid media system? We consider such factors affecting political journalists’ self-identification as recruiting organization and its founders’ proximity to the power structures, pool of experts, party allegiance and journalist’s skills including the level of technological equipment and understanding the modern network principles of the life of information.Conclusion. Due to the increasing amount of information social uncertainty is rising and it is becoming harder and harder to forecast media impact on the public consciousness. Studies among journalists in Russia, Europe and USA show that professional selfidentification is blurred within personal, professional and virtual roles and results in hybrid identity that sometimes consists of mutually exclusive values. It is possible to suggest that structure changes in professional identity structure will affect the components of professionalism in the future.